Pengaruh COVID-19 terhadap Perkembangan Minat Bahasa dan Sastra Korea di Indonesia - Putri, Ajeng Adinda (Universitas Gadjah Mada, 2025)
The COVID-19 pandemic, which began in late 2019, significantly changed daily life and learning behaviors worldwide. In Indonesia, lockdown policies and extended periods of home confinement led many individuals to engage with digital entertainment and online learning platforms. One notable trend during this time was the increased interest in Korean popular culture (Hallyu), including K-pop, dramas, and webtoons. This exposure sparked a growing enthusiasm for learning Korean, often as a means to access and better understand Korean literature and cultural content. This study aims to examine how the COVID-19 pandemic influenced Indonesian society's heightened interest in learning Korean and exploring Korean literature. Using a descriptive quantitative method, data was collected through an online survey of 40 respondents. The study analyzes various aspects of Korean language learners and their interest in Korean literature. The results indicate that the pandemic has played a significant role in fostering interest in both the Korean language and literature. These findings are consistent with Ryan and Deci's (2000) theory of learning motivation, Krashen's (1982) second-language acquisition theory, and Vygotsky's (1978) sociocultural theory. Furthermore, 80% of respondents expressed interest in Korean literature, supporting Lee's (2020) view of a reciprocal relationship between language and literature. Consequently, the increased focus on language learning during the pandemic has also led to a greater interest in Korean literature.